1986
DOI: 10.1002/zaac.19865431209
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und Strukturdaten von „Delafossiten”︁ CuMO2 (M = Al, Ga, Sc, Y)

Abstract: Durch Feststoffumsetzung aus den binären Komponenten wurden 2H‐CuScO2, R‐CuGaO2 und R‐CuYO2 erstmals dargestellt und ihre Kristallstrukturen bestimmt sowie diejenigen von R‐CuAlO2 und 2H‐CuAlO2 verfeinert. Charakteristische Strukturparameter (Gitterkonstanten und Bindungsabstände) werden im Hinblick auf mögliche Cu+Cu+‐Wechselwirkungen diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
50
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 14 publications
12
50
0
Order By: Relevance
“…The calculated bond lengths for each material are in good agreement with experimentally determined measurements. 22,[58][59][60] The lattice parameter a increases for Al-Cr-Sc-Y, consistent with the trend in the cation M III sizes. It has been suggested that the larger M III cations can improve the capacity of a material for extrinsic doping on the M III site, which can result in high hole concentrations, 33 and this has been used to explain the more promising p-type conductivity of doped CuScO 2 and CuYO 2 compared to that of the smallest cation CuAlO 2 .…”
Section: A Structuresupporting
confidence: 61%
See 1 more Smart Citation
“…The calculated bond lengths for each material are in good agreement with experimentally determined measurements. 22,[58][59][60] The lattice parameter a increases for Al-Cr-Sc-Y, consistent with the trend in the cation M III sizes. It has been suggested that the larger M III cations can improve the capacity of a material for extrinsic doping on the M III site, which can result in high hole concentrations, 33 and this has been used to explain the more promising p-type conductivity of doped CuScO 2 and CuYO 2 compared to that of the smallest cation CuAlO 2 .…”
Section: A Structuresupporting
confidence: 61%
“…Two alternative layer stackings are possible, resulting in a hexagonal ͑space group P63/ mmc͒ or rhombohedral ͑space group R3-mh͒ unit cell. 22 It is well known that doping the trivalent metal site with a divalent dopant significantly improves the conductivity, 1 but the trends seen for different trivalent metal cations from Al to Cr to Sc to Y ͑in increasing ionic radius͒ remains a mystery. Nagarajan et al 21 24 Recently, copper delafossites have been the recipient of a lot of theoretical analysis, but this has focused on band gap features, defect energetics, and the effect of doping on the band structure, and to a certain extent has neglected to look at the detailed electronic structure of these materials.…”
mentioning
confidence: 99%
“…The 2H variant has a hexagonal structure (space group Pô^/mmc) with AABB stacking of the oxygen layers. Some ABOj compounds are known to crystallize both in the 3R and 2H structures (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygens in these O-Cu-O units are also each coordinated to three M III atoms, oriented such that M III -centered octahedra form M III O 2 layers which lie parallel to the ab plane. Two alternative layer stackings are possible, resulting in a hexagonal (space group P63/mmc) or rhombohedral (space group R3-mh) unit cell, 14 with CuCrO 2 found to crystalize in both polymorphs. 15,16 It is well known that doping the trivalent metal site in the delafossite structure with a divalent dopant significantly improves the conductivity, 17 but the conductivity trends seen for different trivalent metal cations have remained contentious.…”
mentioning
confidence: 99%